2022
DOI: 10.3389/fbioe.2022.831647
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Hip Center Position Associated With the Range of Internal Rotation and Extension During Gait in Hip Dysplasia Patients After Total Hip Arthroplasty

Abstract: Background: Total hip arthroplasty (THA) for hip dysplasia patients is sometimes complex and compromises pathomorphological changes in these patients. However, it remains unclear whether it is preoperative deformities or postoperative structures or anatomic changes during THA that have the most remarkable correlation with the hip dynamic function during gait. The purpose of this study was to investigate this relationship and propose insights into the surgical reconstruction strategy in patients with developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Elevated hip centers have been reported to lead to a less extended ROM of the affected side in patients during gait ( 20 ). A similar negative regression relationship between center height and extension range was also observed by Hu et al ( 46 ). While in our study, different results were found that a distally placed HRC was associated with increased SI values for adduction-abduction in the frontal plane.…”
Section: Discussionsupporting
confidence: 87%
“…Elevated hip centers have been reported to lead to a less extended ROM of the affected side in patients during gait ( 20 ). A similar negative regression relationship between center height and extension range was also observed by Hu et al ( 46 ). While in our study, different results were found that a distally placed HRC was associated with increased SI values for adduction-abduction in the frontal plane.…”
Section: Discussionsupporting
confidence: 87%
“…However, if the decreased acetabular offset was not compensate and only the original femoral offset was restored, the global offset will be reduced. Several studies have reported that change of the hip centre affect the biomechanics of the hip 27 , 28 . To maintain global offset, medialization should theoretically be compensated for by an equivalent increase in femoral offset 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, Dou et al (2013) found that acetabular revision increased HCOR elevation, thus resulting in leg length differences. Hu et al (2022) found that laterally or superiorly placed HCOR would increase abnormal extension and internal rotation, resulting in impaired gait patterns. These aspects need attention, especially for largely HCOR elevation in acetabular revision.…”
Section: Discussionmentioning
confidence: 96%
“…This also reminds us that upshifting the HCOR will increase the load pressure, thus increasing the wear of the prosthesis due to increased friction at the interface. In addition, the HCOR elevation will lead to differences in the leg length and postoperative kinematics ( Karaismailoglu et al, 2019 ; Hu et al, 2022 ). In a retrospective study, Dou et al (2013) found that acetabular revision increased HCOR elevation, thus resulting in leg length differences.…”
Section: Discussionmentioning
confidence: 99%